Identification of Interspecific and Intraspecific Single Nucleotide Polymorphisms in Papaver spp - Bae, Seon-Hwa; Oh, Jae-Hyeon; Lee, Jundae (Plant breeding and biotechnology, 2021)
The plants of the Papaveraceae family are used for ornamental purposes because of their varicolored flowers, and areknown as medicinal crops. Some species of poppy are used in foods such as salads or sorbets, utilizing the seeds, leaves, pedicels, andpetals. There are several morphological similarities among the species of this family, which make it difficult to distinguish the seeds ofdifferent species or identify opium poppies. The family is known to contain about 100 species. The leaves of Iceland poppy (Papavernudicaule) cultivars with five different flower colors (white, yellow, pink, orange, and scarlet) were sequenced to obtain transcriptomedata. Sequencing was done on plants in three different developmental growth stages (leaf rosette, branching and elongation ofinternodes, and blossom and seed formation). Systematic bioinformatics analysis was conducted to identify single nucleotidepolymorphisms (SNPs) unique to the five Papaver nudicaule cultivars and two other Papaver species (Papaver rhoeas and Papaversomniferum). A 739-Mb reference transcriptome (94.6% BUSCO completeness score) from a 566-Gb RNA-sequencing (RNA-Seq)dataset was obtained. Likewise, 18 significant SNPs were identified to authenticate the three species and five cultivars of Papaver. Thisstudy will facilitate future Papaver research, including evaluation of the results for more detailed characterization. KCI Citation Count: 1